VD_FINDINFO Jug / 2020 / 193 vom 21. Januar 2020 - VD Tribunal cantonal (2020)
INJURE, LÉSION CORPORELLE SIMPLE, CONSTATATION DES FAITS, FIXATION DE LA PEINE | 123 ch. 1 CP, 126 CP, 15 CP, 16 CP, 177 al. 2 CP, 47 CP, 48 let. c CP, 10 CPP (CH)